Urban Health for the Development of Healthy Cities in Indonesia - Christian, Deyo Alfa; Bachtiar, Adang; Candi, Cicilya (Universitas Muhammadiyah Sidoarjo, 2023)
Sustainable urban development, healthy cities and rapid urban growth have become a major focus in Indonesia. This research aims to identify the key factors needed to achieve optimal Urban Health in Indonesia. Currently, DKI Jakarta Province is the largest metropolitan city in Indonesia, but in 2022 DKI Jakarta will be ranked 238th in the world and 48th in Asia regarding the Quality of Life Index. A symbol of success and progress in the country of Indonesia, there are 98 cities spread across all provinces, but only 8 cities are included in the metropolitan category. This research uses the PRISMA extension for Scoping Review (PRISMA-ScR) guidelines, 93 articles published between 2000 and 2022 meet the inclusion criteria that look at Urban Health for city development. In an effort to build a healthy city, Urban Health needs to be implemented using several key factors that encourage good urban health. The policy approach in Indonesia must be to improve the quality and accessibility of health services which are important factors in the effectiveness of urban health services, so as to achieve good urban health. well in Indonesia requires a holistic approach that includes green energy, a clean environment, high levels of physical activity and good stress management, adequate health services, good nutrition and equitable health.